Office Lean : understanding and implementing Flow in a professional and administrative environment - Eakin, Ken (New York : Productivity Press, 2019)
Lean has proven itself as an exceptional business system in manufacturing and a variety of other sectors, such as supply chain, retail, and healthcare. Where Lean has not yet made much of an impact is in professional "white-collar" industries such as banking and insurance, technology services, or government. Why? It is not, as many have assumed, a matter of Lean being irrelevant to "knowledge work," but rather a problem of it being poorly understood and therefore poorly applied in professional office settings. This book closes the gap between Lean's promise, on the one hand, of innovation, business growth, and sustainable competitive advantage; and, on the other, the too frequent reality of Lean's application ending in disappointing results. While nearly every major professional business -- including the digital giants like Apple, Google and Amazon -- has attempted to apply Lean concepts in some way (sometimes under the name Agile), its practice in white-collar industries typically ends up being limited to a small bunch of highly-specialized experts making small, fairly inconsequential improvements in isolated areas, leaving leaders wondering how to make Lean's transformative potential work on a broader basis. The purpose of the book is to help Lean practitioners (both leaders/managers and coaches/consultants) who work in professional office environments gain purchase on the amazing, transformative results Lean can bring to all companies. Overturning the common perception that Lean is about imposing overly rigid rules, or eliminating waste, the book presents Lean as a dynamic, flexible, people-centric philosophy that delivers outstanding financial results by improving both employee engagement and customer experience. The book explains, in simple terms, what Lean is -- and what Lean isn't -- enabling office professionals to understand how it can be successfully applied to their complex office-based work environments. It combines practical explanations of the most important core concepts of the Lean philosophy with relevant, practical, real-world examples from the fields of accounting, finance, insurance, IT, HR and government.
OCLC-licensed vendor bibliographic record.
Keywords: Lean manufacturing; Organizational effectiveness; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Quality Control